Promotional Strategy Of The Tourism Office Of The City Of Bukittinggi In Increasing Tourist VisitsThrough Pedati Events - Diki Hendrian (i-Tourism: Jurnal Pariwisata Syariah, 2025)
The main problem in this thesis is the promotional strategy of the Bukitinggi City Tourism Office in increasing tourist visits through cart events. The aim of this research is to determine the promotion strategy of the Bukittnggi City Tourism Office in increasing tourist visits through cart events.The type of research that the author uses is descriptive qualitative data collection techniques through interviews and documentation. The data analysis technique uses the stages of data reduction analysis, data presentation, and drawing conclusions. The data validity technique uses data source triangulation.Based on research conducted by the author in the field, it can be found that the promotion strategy of the Bukitinggi City Tourism Office is to increase tourist visits through cart events. is to use the theory of Basu Swastha and Irawan. The results of the research show that the Bukittinggi City Tourism Office carries out advertising by placing billboards at every road intersection in Bukittinggi City and also using videotrons, for personal selling the Bukittinggi City Tourism Office makes visits to events outside the City of Bukittinggi, while for Publicity the Tourism Office Bukttinggi City invites Minang artists and influencers to attract tourists to come to the cart event. Not only advertising, personal selling and publicity, the Bukittinggi City Tourism Office also uses sales promotions as a sales promotion strategy by giving free tickets to visitors who will come to the event. cart. The results of the author's analysis regarding the promotion strategy carried out by the Bukittinggi city tourism office through a promotion mix, the strategy applied is almost the same. All of them provide results that are not yet effective in increasing the number of tourist visits, however, what is quite effective and contributes to attracting tourists to come to the cart event is the sales promotion they carry out through free tickets.